Ultrasound-assisted synthesis of substituted guanidines from thioureas - Mookda Pattarawarapan (2018)
© 2016 Elsevier Ltd Ultrasound-assisted synthesis of guanidine derivatives was developed using 2,4,6-trichloro-1,3,5-triazine as an inexpensive dehydrosulfurization reagent. Both 1,3-alkylaryl- and 1,3-diaryl-thioureas were rapidly converted into carbodiimides before subsequent reaction with aromatic or aliphatic amines. The method allows rapid access to highly substituted guanidines in good to excellent yields under mild conditions and with minimal use of solvent.